A Survey on Clustering Protocol LEACH using Static Deployment Technique for WSN - khralkar, Priyanka (International Journal of Computer Sciences and Engineering, 2015)
Advance wireless sensor network (WSN) technology is Low- power electronics and Low-power radio frequency design has enabled the development of small, relatively inexpensive & low-power sensor technology. The important challenges in design of network are three key resource1) Energy 2) Communication bandwidth 3)coverage area . LEACH (Low Energy Adaptive Clustering Hierarchical) is a hierarchical clustering algorithm. It is more efficient than proactive n reactive protocol. LEACH protocol have some disadvantage. To overcome disadvantage we improved LEACH protocol by using optimal path forwarding algorithm and multihop technique i.e O-LEACH protocol. O-LEACH is more efficient than LEACH protocol and it uses static deployment technique.